A novel plasmonic nanostructure for localized near-field light enhancement - Duarte, Maria Inês Caramelo (2020)
The combination of plasmonic structures with dielectric materials, metallic oxides and in particular, with two dimensional (2D) materials has been a subject of great interest in the scientific community for a wide range of applications, such as optoelectronic devices, solar cells, or photochemistry. Plasmonic properties have the potential to enhance the capabilities of 2D materials for harvesting light, which alone have a low efficiency due to low absorption (approximately only 11%). This work presents a new plasmonic structure, “nanohippo” with a perspective to integrate a monolayer material inside the cavity, being this nanostructure directly excited by the incident light taking advantage of localized surface plasmonic resonance (LSPR). The samples were prepared by colloidal lithography and material deposition was made through an electron beam assisted evaporation system. A fabrication method was developed to create a cavity by using a sacrificial material and etching it later on. The sample’s characterization consisted in a morphologic analysis by Scanning Electron Microscopy (SEM), the optical response was studied both theoretically and experimentally by Finite-difference-time-domain (FDTD) as well as experimentally by spectrophotometry. Finally, an elemental analysis was performed via X-ray photoelectron microscopy (XPS). The diameter and height of the structures were studied (different sizes nanoparticles and thicker layers of bottom layer gold) reaching to a structure that presented a plasmonic cavity. This nanostructure, with a new geometry, presented a visible plasmonic nanocavity with up to sixty times more enhancement of the electrical field inside it.